Meta-analysis of present-bias estimation using convex time budgets - Taisuke Imai; Tom Rutter; Colin Camerer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We examine 220 estimates of the present-bias parameter from 28 articles using the Convex Time Budget protocol. The literature shows that people are on average present biased, but the estimates exhibit substantial heterogeneity across studies. There is evidence of modest selective reporting in the direction of overreporting present-bias. The primary source of the heterogeneity is the type of reward, either monetary or non-monetary reward, but the effect is weakened after correcting for potential selective reporting. In the studies using the monetary reward, the delay until the issue of the reward associated with the "current" time period is shown to influence the estimates of present bias parameter.
Keywords: D90; C91; 330; present bias; structural behavioral economics; meta-analysis; selective reporting